Pengaruh Kompensasi, Mutasi, Motivasi, dan Lingkungan Kerja Terhadap Kinerja Guru Sekolah Dasar di Kabupaten Kepulauan Anambas - Asiah Asiah; Sri Langgeng Ratnasari; Etty Puji Lestari (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine and analyze the influence of compensation, mutation, motivation, and work environment on teacher performance in primary schools in the Anambas Islands. The type of research used in this study is quantitative research. The population in this study was 258 Primary School Civil Servant teachers from 10 Districts in the Anambas Islands Regency. The sampling technique uses simple random sampling technique so that it produces 72 respondents. Data source used is primary data. Data collection techniques used questionnaires. Data analysis techniques used are classical assumption test, hypothesis testing and multiple linear regression test. The results showed that the compensation variables have a positive and significant effect on teacher performance, mutations have a positive and significant effect on teacher performance, motivation has a positive and significant effect on teacher performance and the work environment has a positive and significant effect on teacher performance. Simultaneously the variables of compensation, mutation, motivation and work environment have a positive effect on Teacher Performance, this is shown by the value of Adjusted R Square of 0.615 or 61.5%. while the remaining 38.5% was influenced by other factors not included in this study.